Questions of King Milinda - Davids, T. W. Rhys, tr.; Muller, F. Max, ed. (Delhi Low Price, 1996)
Contents: pt.1. (xlix, 320 p.), pt.2. (xxvii, 388 p.).
Library has part I only
Includes index
Keywords: Oriental literature -- Translations into English; Sacred books